2018
DOI: 10.5194/tc-12-3535-2018
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring snow depth change across a range of landscapes with ephemeral snowpacks using structure from motion applied to lightweight unmanned aerial vehicle videos

Abstract: Differencing of digital surface models derived from structure from motion (SfM) processing of airborne imagery has been used to produce snow depth (SD) maps with between ∼ 2 and ∼ 15 cm horizontal resolution and accuracies of ±10 cm over relatively flat surfaces with little or no vegetation and over alpine regions. This study builds on these findings by testing two hypotheses across a broader range of conditions: (i) that the vertical accuracy of SfM processing of imagery acquired by commercial low-cost unmann… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 34 publications
(76 reference statements)
2
41
1
Order By: Relevance
“…Snow is challenging for building products from Structure from Motion (SfM) algorithms because of the high reflectance of homogenous surfaces and lack of contrast. True to photogrammetric theory, limited variation in surface features could hinder SfM software in identifying tie points to match between images, leading to increased inaccuracy or failure to utilize images within an orthomosaic [94]. Because of this, Bühler et al [34] suggested fresh snow to be less suitable than older, weathered snow for reliable photogrammetry.…”
Section: Uavs For Snow Researchmentioning
confidence: 99%
“…Snow is challenging for building products from Structure from Motion (SfM) algorithms because of the high reflectance of homogenous surfaces and lack of contrast. True to photogrammetric theory, limited variation in surface features could hinder SfM software in identifying tie points to match between images, leading to increased inaccuracy or failure to utilize images within an orthomosaic [94]. Because of this, Bühler et al [34] suggested fresh snow to be less suitable than older, weathered snow for reliable photogrammetry.…”
Section: Uavs For Snow Researchmentioning
confidence: 99%
“…In general, the precision of the SFM DEMs is related to flying height, distance to GCP, and image overlap (Goetz et al, 2018;James, Robson, Smith, et al, 2017), as well as field site conditions (Bühler, Adams, Bösch, et al, 2016;Nolan et al, 2015). That is, errors in the computed snow depths can also vary temporally due to different snow-cover conditions (Adams et al, 2018;Bühler, Adams, Bösch, et al, 2016;Fernandes et al, 2018;Harder et al, 2016). The precision for most of the study area was less than 4 cm (at 1σ).…”
Section: Water Resources Researchmentioning
confidence: 99%
“…Adding oblique imagery instead of using only nadir viewing angles or including more images (e.g., higher image overlap) can improve the quality of SFM reconstruction without having to rely solely on GCPs for mitigating SFM reconstruction errors (James & Robson, 2014;James, Robson, d'Oleire-Oltmanns, et al, 2017). Additionally, the density of the GCP network can be further reduced with the use of RTK or post-processing kinematic solutions for correction of the UAVs onboard GNSS for higher-quality camera location estimates (Fernandes et al, 2018;James, Robson, d'Oleire-Oltmanns, et al, 2017). Therefore, by surveying with a strong image network, using high-quality geotagging and ground control (e.g., RTK/PKK GNSS measurements), large-scale SFM snow depth mapping is likely more feasible.…”
Section: Reducing Sfm Snow Depth Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The primary drawbacks of UAS SfM as compared to lidar for mapping snow depth are that the DSM needs to be georeferenced using ground control points (GCPs) with known coordinates and may require significant manual steps (Tonkin et al, 2016;Meyer and Skiles, 2019), although new 85 techniques are emerging that may reduce field data collection time (Gabrlik et al, 2019;Meyer and Skiles, 2019). Dense canopy or vegetation can reduce performance when snow compresses the vegetation relative to the snow-off imagery or when above-canopy vegetation is falsely interpreted to be the snow surface (Bühler et al, 2017;Cimoli et al, 2017;De Michele et al, 2016;Fernandes et al, 2018;Harder et al, 2016;Nolan et al, 2015). Canopy effects impact SfM snow mapping capability in regions where shallow snowpacks are masked by dense forest canopies like the northeastern United 90…”
mentioning
confidence: 99%